Acorns (Quercus rotundifolia Lam.) and grass as natural sources of antioxidants and fatty acids in the “montanera” feeding of Iberian pig: Intra- and inter-annual variations - Tejerina, D.; García-Torres, S.; Cabeza de Vaca, M.; Vázquez, F. M.; Cava, R. (Food Chemistry, 2011)
In two consecutive years (2006/2007 and 2007/2008), fortnightly samples were taken to characterise the antioxidant composition and fatty acid proﬁle of acorns and grass on which Iberian pigs feed during the period of ‘‘montanera” (free-range rearing system of the south-western of Iberian Peninsula). The antioxidant parameters analysed were: a- and c-tocopherol, total phenolics compounds (TPC), lipophilic and hydrophilic antioxidant activities (LAA, HAA) (acorn and grass) and condensed and hydrolysable tannins (CT, HT) and protein precipitating capacity (PP) (acorns). To characterise the fatty acid proﬁles, the thirteen major fatty acids were assayed. For the acorns, it was found that there was intra-annual variability in all the antioxidants studied except a-tocopherol, and inter-annual variability in all except the protein precipitating capacity. The fatty acid proﬁle also varied depending on the sampling date and the study year, especially in the saturated fatty acids (SFA) and C18:1 n-9 content. For the grass, there was intraand inter-annual variability in all the antioxidant parameters studied, and in the proportions of the fatty acids C18:0, and C18:1. It could explain variations in the antioxidant and fatty acids composition of Iberian pig tissues from animals raised in different ‘‘montanera” seasons and even in the same ‘‘montanera” season.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorn; antioxidant; fatty acid; Grass; iberian pig; ‘‘Montanera”

Growth performances , carcasses parameters and meat fatty acid composition of lamb fed green oak acorns ( Quercus ilex ) based diet - Keddam, Ramdane; Bouderoua, Kaddour; El-affifi, Mohamed; Attou, Ghalem Selselet- (African Journal of Biotechnology, 2010)
The aim of this experiment is to compare the effects of diets containing green oak acorns (GO) and barley (BL) on the growth performances, carcasses parameters and the composition in fatty acids of lambs. Two groups of five lambs each were fed, respectively, during 105 days with diets containing 50% of oaks acorns and 50% of barley. At the end of the test, the animals of the two diets expressed comparable body weights and weight gain. A significant difference (P < 0.05) was observed for the thickness of fat cover which is 3 mm for the BL group against 1.6 mm for GO group even if no significant difference was revealed concerning the output with slaughtering. The intramuscular lipids were significantly higher (P < 0.05) in the group of animals fed with GO diet compared to the BL diet (3.88 vs 2.83 g.100-1 g of muscle). Among the saturated fatty acids (SFA), the stearic acid significantly appeared in higher proportion (P < 0.05) in GO diet (20.8 vs 18.1%) whereas the palmitic acid is prevalent in the group of animals fed with the BL diet (25 vs 30%). For the polyunsaturated fatty acid (PUFA), no significant difference was observed between the two groups. The linoleic acid is prevalent among the PUFA of two groups without significant difference. The linolenic acid is higher in the animal fed BL. The n-6: n-3 ratio is higher in the BL group (8.9 vs 7.3). At the end, the low level of incorporation of PUFA in muscle of the lamb because of biohydrogenation, suggests us supplementing the diet by green grass.
Keywords: barley; fatty acid; lamb; meat; oak acorn

Effect of mediterranean forest parasite with Curculio sp. on nutritional value of acorn for Iberian pig feeding and fat characteristics. - Daza, a; López-Bote, C J; Tomás Barberán, F a; Espin, J C; López Carrasco, C; Olivares, A; Rey, a I (Meat science, 2007)
Sixteen Iberian barrows of the same age with an average initial live weight of 100.1kg were randomly distributed in two groups of eight pigs each. One group was fed healthy acorns and the other group received acorns infested of Curculio sp. The subcutaneous backfat from pigs fed healthy acorns had higher C18:1n-9, MUFA and C20:5n-3 and lower C18:0 and SFA proportions than that from the pigs fed acorns infested with Curculio. The consumption of acorns infested with Curculio sp. led to a reduction of C18:1n-9, MUFA, C18:2n-6, C18:3n-3, C22:5n-3 and PUFA proportions in neutral lipids from Longissimus dorsi muscle with respect to consumption of healthy acorns, whereas in polar lipids it produced a reduction in C18:1n-9, MUFA and C18:4n-3 proportions and an increase in C18:2n-6, C20:4n-6, n-6 and C20:5n-3 proportions and of n-6/n-3 ratio with respect to the healthy acorns consumption. The pigs fed healthy acorns had higher intramuscular fat percentage in Longissimus dorsi than pigs fed with acorns infested with Curculio (9.95 vs 7.09% SEM=0.60).
Keywords: Curculio; fat; fatty acid; iberian pig

Effect of mediterranean forest parasite with Curculio sp. on nutritional value of acorn for Iberian pig feeding and fat characteristics. - Daza, a; López-Bote, C. J.; Tomás Barberán, F. a; Espin, J. C.; López Carrasco, C.; Olivares, A.; Rey, a I. (Meat science, 2007)
Sixteen Iberian barrows of the same age with an average initial live weight of 100.1kg were randomly distributed in two groups of eight pigs each. One group was fed healthy acorns and the other group received acorns infested of Curculio sp. The subcutaneous backfat from pigs fed healthy acorns had higher C18:1n-9, MUFA and C20:5n-3 and lower C18:0 and SFA proportions than that from the pigs fed acorns infested with Curculio. The consumption of acorns infested with Curculio sp. led to a reduction of C18:1n-9, MUFA, C18:2n-6, C18:3n-3, C22:5n-3 and PUFA proportions in neutral lipids from Longissimus dorsi muscle with respect to consumption of healthy acorns, whereas in polar lipids it produced a reduction in C18:1n-9, MUFA and C18:4n-3 proportions and an increase in C18:2n-6, C20:4n-6, n-6 and C20:5n-3 proportions and of n-6/n-3 ratio with respect to the healthy acorns consumption. The pigs fed healthy acorns had higher intramuscular fat percentage in Longissimus dorsi than pigs fed with acorns infested with Curculio (9.95 vs 7.09% SEM=0.60).
The following values have no corresponding Zotero field: accession-num: 22064301
Keywords: Curculio; fat; fatty acid; iberian pig

Acorn (Quercus spp.) fruit lipids: Saponifiable and unsaponifiable fractions: A detailed study - León-Camacho, Manuel; Viera-Alcaide, Isabel; Vicario, Isabel M. (Journal of the American Oil Chemists' Society, 2004)
The composition of the oils extracted from the acorn fruit of three species of Mediterranean oaks, Quercus ilex L., Q. suber L., and Q. faginea L., was characterized. Both major and minor components, including FA, TG, sterols, methyl sterols, triterpenic and aliphatic alcohols, tocopherols, and hydrocarbons, were identiﬁed by standard methods and MS. Highresolution GLC and HPLC were used for quantiﬁcation. The FA profile, together with the equivalent carbon numbers and TG carbon numbers, was compared with data for other edible vegetable oils. Oil yield, expressed as wet weight, was 5% (w/w). Sterol content was remarkable for the three species (8,563–11,420 mg/kg), with β-sitosterol being the most abundant (80%). Oils were also high in tocopherol, with a wide variation between species (165–456 mg/kg) but with γ-tocopherol predominating in all three oils (90% of the total tocopherol content). Also, high terpenic alcohol contents were found (1527–2984 mg/kg), with dammaradienol and β-amyrin being the most abundant (33–60% of the total alcohol content). Bioactive properties and industrial applications of this underutilized native product are also discussed.
Keywords: Acorn oil; fatty acid; hydrocarbons; Quercus spp.; sterols; triglycerides

Susceptibility of hepatic tissue of Iberian pigs is enhanced by free-range feeding and reduced by vitamin E supplementation - López Bote, C. J.; Rey, A. I. (Nutrition Research, 2001)
The effect of feeding system (free-range vs conﬁnement) and the supplementation of concentrated feed with vitamin E and copper was investigated. Dietary copper supplementation (100 mg/kg) increased the hepatic concentration of copper in hepatic tissue (P , 0.05), reaching similar concentrations than pigs fed under free-range conditions. Free-range feeding produced higher concentration of a-tocopherol than those from pigs fed in conﬁnement with the basal level of vitamin E, but lower values than pigs fed supplemented levels, which may be attributed to the relative high concentration of a-tocopherol in the grass. Liver samples from pigs under free-range conditions showed higher susceptibility to lipid oxidation than pigs produced in conﬁnement and fed mixed diets. No signiﬁcant effect of copper was observed in hepatic tissue oxidation, but vitamin E supplementation markedly decreased oxidation
Keywords: a-tocopherol; copper; fatty acid; liver; pig